Dificultăţi ale învăţământului profesional şi tehnic. Studiu de caz: Liceul „Dan Mateescu” Călăraşi - Glăvan, Eugen (Calitatea Vieții, 2016)
The educational services offered by the vocational and technical institutions evolve in a job market characterised by change and diversity. Their quality is influenced by the public policies that also have to respond to demographic challenges. When these elements meet in a social space where opportunities and the variety of job offers are low, the institutions involved in vocational and technical education have to adopt strategies adapted to these realities. In this article we will present the results of a qualitative research carried out in an underdeveloped area, showing how the educational institutions, conditioned by legislation, adapt to the demands of the job market and to the needs of their direct beneficiaries.